Development of a Competency-Based Training Model for Child Friendly Pesantren Teams - Abert Albert; Zulfani Sesmiarni; Arman Husni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
His study aims to develop a valid, practical and effective competency-based training model for Child-Friendly Pesantren Teams. The method used is the research and development method with the ADDIE model (Analyze, Design, Develop, Implementation, and Evaluation). The products development result and their validity value encompassing 1) Book model which explains the concept of a competency-based training model┬á with the validity value was K = 0,86 (very high); 2) TrainerÔÇÖs guidance book in which itsÔÇÖ validity value achieving ┬á┬á┬á┬á┬á┬á┬á┬á┬á┬áK = 0,88 (very high); and 3) TraineesÔÇÖ book which achieved the score of K=0,87 (very high). It was proved that the model that has been developed was very practical with the average value of K=0,95 (very high), and could significantly increase participantsÔÇÖ competency in comprehending the training materials of with a sig value of 0.00< 0.05. It is concluded that the developed model proved to be valid, practical, and effective. This research implies that the PE-ADI model is feasible to be applied in training child friendly pesantren teams. It is recommended that 1) the child friendly pesantren teams at the central and provincial levels socialize that training model to pesantren in Indonesia; 2) the implementation of the training model follows the references in the modelÔÇÖs book, trainerÔÇÖs book and participantsÔÇÖ book.